Web based Application for Presentation of Bulgarian Cultural and Historical Heritage under the Protection of UNESCO - Stefka Kovacheva; Ludmila Dimitrova (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2019)
The paper briefly describes the web based application “Me and UNESCO” for the realization of the database “Bulgarian cultural and historical heritage under the protection of UNESCO”, developed in IMI (BAS). The web based application follows a modern learning strategy based on the Understanding by Design approach. In a multimedia environment, additional content is provided on study topics commenting on the Bulgarian cultural and historical heritage sites under the protection of UNESCO.